Human resources who competen The Influence Of Human Resource Competence In Spencer's Concept To Organizational Entrepreneurship - Dyah Pikanthi Diwanti; Muhsin Hariyanto (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Background – Organizational entrepreneurship is one of the solutions used to maintain the existence and sustainability of an organization oriented towards community empowerment in Indonesia. Aim – This study aims to analyze the effect of human resource competence using the Spencer model on organizational entrepreneurship. Design / methodology / approach – The research respondents were all 35 female partners at BUANA. Collecting data using questionnaires and interviews. The modified human resource competency instrument from the Spencer Model, and Organizational Entrepreneurship uses an adaptation instrument from Spencer and Spencer's initial research. The analytical tool used to measure the level of data validity is the correlation coefficient using SPSS17.0 software. Result and Discussion – The results of the study indicate that the competence of Spencer's human resources concept which consists of motivation, nature, attitude, knowledge and skills has a very important role in the effort to develop Organizational Entrepreneurship. Organizational entrepreneurship is found in various organizations in the community and can increasingly provide space in driving economic activity in the community and groups/organizations. Conclusion - Based on the results above, the value of HR Competence with Organizational Entrepreneurship shows a linearity significance so HR Competence was linear with Organizational Entrepreneurship. This coherence with HR Competencies affected Organizational Entrepreneurship.